Chemokine Expression Is Involved in the Vascular Neogenesis of Ewing Sarcoma: A Preliminary Analysis of the Early Stages of Angiogenesis in a Xenograft Model. (January 2019) - Giner, Francisco; López-Guerrero, José A; Fernández-Serra, Antonio; Machado, Isidro; Mayordomo-Aranda, Empar; Peydró-Olaya, Amando; Llombart-Bosch, Antonio
Background: Ewing sarcoma (EWS) is the second most common bone cancer in pediatric patients. Angiogenesis is a major factor for tumor growth and metastasis. Our aim was to carry out a histological, immunohistochemical, and molecular characterization of the neovascularization established between xenotransplanted tumors and the host during the initial phases of growth in nude mice in three angiogenesis experiments (ES2, ES3, and ES4). Methods: The original human EWS were implanted subcutaneously on the backs of three nude mice. Tumor pieces 3 mm–4 mm in size from early passages of Nu432, Nu495, and Nu471 were also implanted subcutaneously on the backs of three sets (ES2, ES3, and ES4) of athymic Balb-c nude mice (n = 14 each). The animals were sacrificed at 24, 48, and 96 hours and at 7, 14, 21, and 28 days after implantation to perform histological, immunohistochemical, and molecular studies (neovascularization experiments). Results: We observed histological, ultrastructural, and immunohistochemical changes in the xenografted tumor at different times after implantation. Chemokine ligand expression peaked twice, once during the first 48 hours and again in the second week. We observed that tumor cells in contact with murine peritumoral stroma presented higher expression of chemokine ligands as well as more tumor cells around the capillary vessels. Mouse serum vascular endothelial growth factor levels peaked twice, once in the first hours and then in the second week after tumor implantation. Conclusion: Chemokines and other angiogenic factors may be relevant in the angiogenic mechanism during tumor growth. This model provides information on the early stages of the angiogenic process and could be a useful tool in researching anti-angiogenic drugs for new therapeutic strategies in EWS.